ALTERED ACTIVATION OF THE ROSTRAL ANTERIOR CINGULATE CORTEX IN THE CONTEXT OF EMOTIONAL FACE DISTRACTORS IN CHILDREN AND ADOLESCENTS WITH ANXIETY DISORDERS. Issue 10 (3rd July 2014) - Swartz, Johnna R.; Phan, K. Luan; Angstadt, Mike; Klumpp, Heide; Fitzgerald, Kate D.; Monk, Christopher S.
<x xml:space="preserve">Abstract</x> Background Pediatric and adult anxiety disorder patients exhibit attention bias to threat and difficulty disengaging attention away from threat. Cognitive frameworks suggest that these patterns are associated with hyperactivation of regions associated with detecting threat, such as the amygdala, and hypoactivation of regions associated with regulating attention, including the lateral prefrontal cortex and rostral anterior cingulate cortex (rACC). The aim of the present study was to examine the neural correlates of these processes in children and adolescents with anxiety disorders. Methods Participants with an anxiety disorder 7 to 19 years old (n = 34) and typically developing controls (n = 35) underwent fMRI scanning. During scanning, they completed a task with conditions that manipulated whether participants were instructed to match emotional faces (direct emotion processing) or match shapes in the context of emotional face distractors (attentional control). Results Results revealed a significant difference in rACC activation during shape versus face matching, with controls evidencing greater rACC activation relative to patients. Conclusions This study identifies abnormalities in rACC activation as a potential neural mediator associated with pediatric anxiety disorders, which can inform frameworks for understanding their development and treatment.